Perancangan Katalog Gua Maria Puhsarang Sebagai Media Informasi Pariwisata Religi Di Kabupaten Kediri - Ignasius Jeksianus Iko; Pujiyanto Pujiyanto; Rina Nurfitri (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
Maria Puhsarang Cave in Kediri has a very interesting charm of beauty to visit. Its beauty is seen because of rice fields and plantationresidents and has a cool air temperature because it is located under the slope of Mount Wilis. Maria Puhsarang cave suffers from many shortcomings, including no explanation or information about the existing building that makes the visitors confused. In fact, the explanation of each of the buildings can be useful communication tools. Therefore, it takes a media that can answer the shortcomings, which is an information media that can provide infomation about the circumstances and buildings in the Maria Puhsarang Cave.The design method begins with a background research of the problem and then resumes with data collection, consisting of primary dataand secondary data. Furthermore, the analysis data and synthesis will be conducted, to determine the concept of design and perform the design process to the end of the designs. Thus, this design resulted in a catalogue of photography titled "Gua Maria Puhsarang and quot;, or in English means “Maria Puhsarang Cave”. In this catalogue, the photographs will be arranged in such a way and equipped with a brief description explaining each photograph, so it is hoped that the photography catalogue can be used as one of the tourist information media of the Maria Puhsarang Cave who can provide more information for the tour.